Measurement of Bulk Mechanical Properties of Tissue Using Laser Speckle Rheology - Hajjarian, Zeinab (Conf Proc IEEE Eng Med Biol Soc, 2011)
In virtually all tissues, disease progression is accompanied by changes in the mechanical properties. Laser speckle rheology (LSR) is a new technique we have developed to measure the mechanical properties of tissue. By illuminating the sample with coherent laser light and calculating the speckle intensity modulations from reflected laser speckle patterns, LSR calculates τ, the decay time constant of intensity decorrelation which is closely associated with tissue mechanical properties. In this paper we validate the use of LSR technology in measuring mechanical properties of tissue. LSR measurements of τ are performed on a variety of phantom and tissue samples and compared with the complex shear modulus G*, measured using a rheometer. In all cases, strong correlation is observed between τ and G* (r=0.95, p<0.002). These results demonstrate the efficacy of LSR as a non-invasive and non-contact technology for mechanical evaluation of biological samples.